Study of Road Utility Planning as an Effort to Create an Environmentally Friendly Area on the Jalan Ampera Medan Corridor - Siregar, Zulkifli; Asfiati, Sri; Dewi, Irma (Universitas Ibn Khaldun Bogor, 2024)
Designing the utility planning concept for the Ampera Medan road corridor, it starts with identifying the condition of the drainage system, traffic signs, road markings, public road lighting, and road user safety devices. Furthermore, a study of changes to road utility requirements is carried out by road management guidelines and road environmental conditions in the form of improving kindness on the road surface, installing signs and warning devices, installing flashing lights, removing roadblocks, and installing noise tape based on certain distances. This research aims to produce a design concept for road utility planning that is environmentally friendly and sustainable (sustainable road) under the guidelines of the Ministry of PUPR while still paying attention to basic human needs and economic growth. Research and knowledge related to the concept of environmentally friendly road utility planning on the Jalan Ampera Medan corridor is a contribution to scientific work that can provide benefits to the Muhammadiyah University of North Sumatra and the Medan City Government as material for consideration and decisions in the construction of environmentally friendly roads (green roads) in the city Medan.